Pengembangan Media Pembelajaran Matematika Berbasis Google Sites pada Materi Program Linier - Agustina Jari; istiqomah; Irham Taufiq (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to develop google sites-based mathematics learning media on linear program material because it is uploaded to Google sites are not easily lost and will be archived properly so that students or teachers do not need to use flash drives which can cause many viruses to enter the computer. Beside that, to determine the feasibility of the google sites media being developed. The research method used is Research and Development (R&D) with the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. The research was conducted at SMA Negeri 11 Yogyakarta with the research subjects being 15 students of class XI IPS 2 by purposive sampling technique. The data collection technique used a questionnaire technique consisting of a validation questionnaire from a media expert, a material expert and a student response questionnaire to a limited field trial conducted online using the WhatsApp group platform. The results of the research are in the form of google sites media named Program_Linear which can be accessed using the link: https://sites.google.com/view/program-linear-sma/home-math . The developed google sites media has met the eligibility criteria for use in the learning process. This is evidenced by the results of the media expert validation obtaining an average score of 4.6 with the very good category, while the results of the material expert validation obtained an average score of 3.6 in the good category, and the results of students' responses to limited trials obtained an average score of 3.5 in the good category.